Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm stuck with this one, so far I've tried taking logarithms to apply "The limit of the logarithm is the $ln$ of the limit" And then turning it into an infinite/infinite indeterminate but keep obtaining $0$ D:

share|cite|improve this question
The limit of the log is $0$, so if $L$ is the desired limit, $\ln L=0$, and $L=~?$ – Brian M. Scott Jan 7 '13 at 22:49
Presumably you want the limit as $x$ approaches $1$ from the right, because of difficulties with the meaning of $a^b$ when $a$ is negative. – André Nicolas Jan 7 '13 at 22:57
up vote 3 down vote accepted

Your limit is of the form $0^0$. In this case, it is helpful to use the fact that $a^b = \exp(b \ln a)$. You then have that (exp is continuous) $$\lim_{x\to 1} (\ln x )^{x-1} = \exp\left[ \lim_{x\to 1} (x-1) \ln\ln(x)\right] =\exp(0) =1$$ because $\ln x$ grows slower than any polynomial.

share|cite|improve this answer

L'Hospital's also a possibility:

$$(\log x)^{x-1}=e^{(x-1)\log\log x}$$


$$\lim_{x\to 1^+}(x-1)\log\log x=\lim_{x\to 1^+}\frac{\log\log x}{\frac{1}{x-1}}\stackrel{\text{L'H}}=\lim_{x\to 1^+}-\frac{(x-1)^2}{x\log x}\stackrel{\text{L'H}}=$$

$$=\lim_{x\to 1^+}-2\frac{x-1}{\log x+1}=-2\frac{0}{0+1}=0$$

Thus the limit is, by continuity of the exponential function, $\,e^0=1\,$

share|cite|improve this answer

Let us first set $u=x-1$. Note that your limit requires $x-1=u>0$ to make sense.

So your limit is equal to $$ \lim_{u\rightarrow 0^+} (\ln (1+u))^u. $$ Now for all $u>0$, we have $$ \ln(1+u)\leq u $$ since the graph of $\ln (1+u)$ is below the tangent at $u=0$ (by a concavity argument).

Using the fact that $\ln$ is increasing on $]0,+\infty[$, we have $$ 1\leq (\ln (1+u))^u=\exp\left( u\ln(\ln (1+u))\right)\leq \exp(u\ln u) $$ for all $u>0$.

It remains to invoke the Squeeze theorem and the fact that $$ \lim_{u\rightarrow 0^+} u\ln u=0 $$ to deduce from the inequality above that your limit is equal to $\exp(0)=1$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.